Voluntary Ambulation by Upper Limb-Triggered HAL® in Patients with Complete Quadri/Paraplegia Due to Chronic Spinal Cord Injury - Shimizu, Yukiyo; Kadone, Hideki; Kubota, Shigeki; Suzuki, Kenji; Abe, Tetsuya; Ueno, Tomoyuki; Soma, Yuichiro; Sankai, Yoshiyuki; Hada, Yasushi; Yamazaki, Masashi (Frontiers in Neuroscience, 2017)
Patients with complete paraplegia after spinal cord injury (SCI) are unable to stand or walk on their own. Standing exercise decreases the risk of decubitus ulcers, osteoporosis, and joint deformities in patients with SCI. Conventional gait training for complete paraplegia requires excessive upper limb usage for weight bearing and is difficult in cases of complete quadriplegia. The purpose of this study was to describe voluntary ambulation triggered by upper limb activity using the Hybrid Assistive Limb® (HAL) in patients with complete quadri/paraplegia after chronic SCI. Four patients (3 men, 1 woman) were enrolled in this study. The mean patient age ± standard deviation was 37.2 ± 17.8 (range, 20–67) years. Clinical evaluation before intervention revealed the following findings: case 1, neurological level C6, American Spinal Cord Injury Association impairment scale (AIS) grade B; case 2, T6, AIS A; case 3, T10 AIS A; and case 4, T11, AIS A. The HAL intervention consisted of 10 sessions. Each HAL session lasted 60–90 min. The HAL electrodes for hip and knee flexion-extension were placed on the anterior and posterior sides of the upper limbs contralaterally corresponding to each of the lower limbs. Surface electromyography (EMG) was used to evaluate muscle activity of the tensor fascia lata and quadriceps femoris (Quad) in synchronization with a Vicon motion capture system. The modified Ashworth scale (mAs) score was also evaluated before and after each session. All participants completed all 10 sessions. Cases 1, 2, and 3 demonstrated significant decreases in mAs score after the sessions compared to pre-session measurements. In all cases, EMG before the intervention showed no apparent activation in either Quad. However, gait phase dependent activity of the lower limb muscles was seen during voluntarily triggered ambulation driven by upper limb muscle activities. In cases 3 and 4, active contraction in both Quads was observed after intervention. These findings suggest that upper-limb-triggered HAL ambulation is a safe and feasible option for rehabilitation in patients with complete quadri/paraplegia caused by chronic SCI.